Body mass index, basal insulin and glycemic control in children with type 1 diabetes treated with the advanced hybrid closed loop system remain stable - 1-year prospective, observational, two-center study - Seget, Sebastian; Jarosz-Chobot, Przemysława; Ochab, Agnieszka; Polanska, Joanna; Rusak, Ewa; Witoszek, Paulina; Chobot, Agata (Frontiers in Endocrinology, 2022)
Background: Information on the influence of insulin treatment using advanced hybrid closed loop systems (AHCL) on body weight of young patients with type 1 diabetes (T1D) is scarce. The aim of this study was to observe whether there were any changes in body mass index (BMI) of children and adolescents with T1D treated using the Medtronic Minimed 780G AHCL after 1 year of follow up and to analyze potential associations between these changes and the insulin doses. Materials and Methods: For 50 children and adolescents (age 5.4-16.8 years, 24 (48%) boys, T1D for 3.9 ± 2.56 years) using an AHCL system anthropometric and AHCL data were collected prospectively. BMI Z-scores and two-week AHCL records obtained after AHCL enrollment were compared with data after 6 months and also 1 year after starting AHCL. Results: The BMI Z-score of the patients at 1 year follow-up did not change from time of AHCL initiation (0.51±2.79 vs 0.57±2.85, p>0.05 ). There was a slight increase in total daily insulin per kg of body weight (0.67 ± 0.21 U/kg vs 0.80±0.21 U/kg, p <0.001), but the percent of basal insulin was unchanged (34.88±6.91% vs 35.08 ±6.30%, p>0.05). We observed also no change (AHCL start vs after 1 year) in glycemic control parameters: average sensor glucose (131.36± 11.04 mg/dL vs 132.45 ±13.42 mg/dL, p>0.05), coefficient of variation (34.99± 5.17% vs 34.06±5.38%, p>0.05), glucose management indicator (6.45 ± 0.26% vs 6.48 ± 0.32%, p>0.05), and time spent in the range of 70–180 mg/dL (79.28 ± 8.12 % vs 80.40 ± 8.25%, p>0.05). Conclusion: During the 1 year of follow-up the BMI of children and adolescents with T1D treated with an AHCL system remained stable. Although there was a slight increase in the total daily insulin dose, the percent of basal insulin was unchanged. The patients maintained recommended glycemic control.